Two new species of the spider genus Agyneta (Araneae, Linyphiidae) from Uruguay and Brazil - Cajade, Manuel; Hagopián, Damián; Rodrigues, Everton N.L. [UNESP]; Laborda, Álvaro; Maldonado, M. Belén; Simó, Miguel (Magnolia Press, 2023)
Agyneta hum Cajade, Rodrigues & Simó n. sp. and Agyneta unguiserrata Cajade n. sp. are described and illustrated from Brazil and Uruguay based on males and females. Males of A. hum differ from the related A. adami (Millidge 1991) by having apical and posterior pocket of paracymbium, presence of dorsal tibial apophysis and the shape and surface of the cymbial tubercles. Females of A. hum differ from A. adami in having the margins of the proximal part of the scape parallel and the presence of a pit hook depression. Males of A. unguiserrata distinguished from all other congeners by having a dorsal tibial apophysis claw-shaped with denticles on the retrolateral margin. Females of A. unguiserrata distinguished from all other congeners by the presence of two elliptical processes in the epigynum. Illustrations of somatic and genital characters and distribution maps of the species are provided. These species constitute the first report of the genus for Uruguay.
Keywords: Atlantic forest; Micronetinae; Neotropics; Pampa biome; taxonomy